Colitis‐induced colorectal cancer and intestinal epithelial estrogen receptor beta impact gut microbiota diversity. Issue 12 (11th January 2019) - Ibrahim, Ahmed; Hugerth, Luisa W.; Hases, Linnea; Saxena, Ashish; Seifert, Maike; Thomas, Quentin; Gustafsson, Jan‐Åke; Engstrand, Lars; Williams, Cecilia
Abstract : Chronic inflammation of the colon (colitis) is a risk factor for colorectal cancer (CRC). Hormone‐replacement therapy reduces CRC incidences, and the estrogen receptor beta (ERβ/ESR2) has been implicated in this protection. Gut microbiota is altered in both colitis and CRC and may influence the severity of both. Here we test the hypothesis that intestinal ERβ impacts the gut microbiota. Mice with and without intestine‐specific deletion of ERβ (ERβKO Vil ) were generated using the Cre‐LoxP system. Colitis and CRC were induced with a single intraperitoneal injection of azoxymethane (AOM) followed by administration of three cycles of dextran sulfate sodium (DSS) in drinking water. The microbiota population were characterized by high‐throughput 16S rRNA gene sequencing of DNA extracted from fecal samples ( N = 39). Differences in the microbiota due to AOM/DSS and absence of ERβ were identified through bioinformatic analyses of the 16S‐Seq data, and the distribution of bacterial species was corroborated using qPCR. We demonstrate that colitis‐induced CRC reduced the gut microbiota diversity and that loss of ERβ enhanced this process. Further, the Bacteroidetes genus Prevotellaceae_ UCG_001 was overrepresented in AOM/DSS mice compared to untreated controls (3.5‐fold, p = 0.004), and this was enhanced in females and in ERβKO Vil mice. Overall, AOM/DSS enriched for microbiota impacting immune system diseases and metabolic functions, and lack of ERβ in combination with AOM/DSS enriched for microbiota impacting carbohydrate metabolism and cell motility, while reducing those impacting the endocrine system. Our data support that intestinal ERβ contributes to a more favorable microbiome that could attenuate CRC development. Abstract : What's new? Chronic inflammation of the colon is a risk factor for colorectal cancer (CRC). Hormone‐replacement therapy reduces CRC incidence, and the estrogen receptor beta (ERβ/ESR2) has been implicated in this protection. The microbiota of the gut is altered in both colitis and CRC, but whether intestinal ERβ affects gut microbiota remains to be investigated. Here, the authors demonstrate, in a mouse model, that colitis‐induced CRC reduces the gut microbiota diversity and that loss of ERβ enhances this process. The findings could enable novel therapeutic or preventive approaches toward a more favorable microbiome in inflammatory bowel disease and/or colon cancer development.